Music in the classroom: reflections on sexuality in basic education - Fernandes, Karina Nonato [UNESP]; Reina, Fabio Tadeu [UNESP]; Mokwa, Valeria M. N. F. [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
This paper aims to bring reflections on music in the classroom and discuss their influence on sexuality. We use the literature to support this work and based on discursive practices carried out by the authors in different social groups, on the theme in vogue. We realize more and more the influence of sexuality through music, which urges us to search reflections about our values and professional performance, so that the child may have development in general based on reflection, critical and reflective construction about these themes proposed here.
Keywords: Music; Sex education; Professional qualification